2018
DOI: 10.1002/brb3.930
|View full text |Cite
|
Sign up to set email alerts
|

The asymmetry of neural symptoms in Wilson's disease patients detecting by diffusion tensor imaging, resting‐state functional MRI, and susceptibility‐weighted imaging

Abstract: ObjectiveTo investigate the cause of the motor asymmetry in Wilson's disease (WD) patients using functional MRI.MethodsFifty patients with WD and 20 age‐matched healthy controls were enrolled. Neurological symptoms were scored using the modified Young Scale. All study subjects underwent diffusion tensor imaging (DTI), susceptibility‐weighted imaging (SWI), and resting‐state functional MRI (rs‐fMRI) of the brain. Six regions of interest (ROI) were chosen. Fiber volumes between ROIs on DTI, corrected phase (CP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…This can mimic essential tremor, a much more prevalent movement disorder that also occurs in young people. Tremor in WD, like dystonia and parkinsonism, can also be asymmetrical (72). Wing-beating tremor refers to a large amplitude postural tremor in the upper limbs that emerges as the elbows are flexed.…”
Section: Tremormentioning
confidence: 99%
“…This can mimic essential tremor, a much more prevalent movement disorder that also occurs in young people. Tremor in WD, like dystonia and parkinsonism, can also be asymmetrical (72). Wing-beating tremor refers to a large amplitude postural tremor in the upper limbs that emerges as the elbows are flexed.…”
Section: Tremormentioning
confidence: 99%
“…Whenever neurologic disorders occur in patients, copper and iron contents are higher than those in patients with only hepatic symptoms [ 118 ]. No correlation has been reported between the asymmetry of CP values in the subcortical nuclei and the motor asymmetry [ 125 ]. Furthermore, a negative correlation has been reported between SWI phase values of GP and the severity of dysarthria, while a negative correlation has been detected between SWI phase values of CN and the extent of tremor [ 120 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In all eight patients, there was damage seen in the caudate nucleus [21]. Another study in 2018 found that patients with choreic movement had marked asymmetry of the ber volumes between the caudate nucleus and the thalamus [22]. The treatment of choreoathetosis is limited to dopamine depletion agents such as tetrabenazine and behavioral therapy.…”
Section: Choreoathetosismentioning
confidence: 98%
“…Like many other neurodegenerative diseases, the tremor can be unilateral or bilateral. A study in 2018 analyzing the tremor of WD found that tremor asymmetry was in uenced by the asymmetry of ber volumes between the thalamus and cerebellum as well as the caudate nucleus and the thalamus [22].…”
Section: Tremormentioning
confidence: 99%